Association between weekend catch-up sleep and hypertension of the United States population from 2017 to 2020: a cross-sectional study - Yan Luo; Qingyuan Li; Qingyuan Li; Tong Feng; Shasha Meng; Shasha Meng; Ran Duan; Ran Duan (Frontiers in Psychiatry)
BackgroundHypertension is a prevalent cardiovascular risk factor that significantly contributes to morbidity and mortality worldwide. Previous studies have highlighted the role of inadequate sleep during weekdays in the development of hypertension. However, the potential mitigative effects of weekend catch-up sleep (WCS) on hypertension have been less explored.MethodsThis cross-sectional study analyzed data from the National Health and Nutrition Examination Survey (NHANES) 2017–2020, focusing on American adults. We assessed the association between WCS (defined as the difference in sleep duration between weekend and weekday) and the presence of hypertension. Participants were classified into two groups based on their WCS duration: none (below 1 hours), yes (over 1 hours). Multivariable logistic regression models adjusted for potential confounders such as age, gender, Body mass index (BMI), and lifestyle factors were utilized to explore this association. A Generalized Additive Model (GAM) was employed to generate smooth curves for a nuanced analysis of the nonlinear relationship.ResultsThe findings indicated that moderate WCS (less than 4 hours) was significantly associated with a reduced risk of hypertension, while excessive WCS (greater than 4 hours) showed no significant protective benefits. ConclusionModerate weekend catch-up sleep could serve as an effective intervention to mitigate hypertension risk, especially in populations with restricted weekday sleep. These results suggest the potential for integrating sleep management strategies into public health recommendations to address hypertension. Future longitudinal studies are needed to confirm these findings and clarify the mechanisms underlying the relationship between WCS and hypertension risk.